Interfered long non-coding RNA HELLPAR or up-regulated microRNA-448 inhibits nasopharyngeal carcinoma progression via suppression of ADAM10 - Wenjuan Zhu; Qi Yang; Huijun Yang; Mingtao Qian; Yan Ji; Jianyong Liu (Discover Oncology)
Abstract Objective Nasopharyngeal carcinoma (NPC) is a highly invasive malignancy with poor prognosis, necessitating further exploration of its molecular mechanisms. While HELLP-associated long non-coding RNA (HELLPAR), microRNA-448 (miR-448), and a disintegrin and metalloprotease 10 (ADAM10) have been implicated in other malignancies, their regulatory interplay and functional roles in NPC remain unclear. This study aimed to investigate the role of HELLPAR in NPC progression through its interaction with miR-448 and ADAM10. Methods Cancerous and adjacent non-cancerous tissues were collected from 53 NPC patients admitted to our hospital between 1st January 2018 and 1st January 2020. Transcript levels of HELLPAR, miR-448, and ADAM10 were measured using quantitative real-time PCR (RT-qPCR), while the protein expression levels of ADAM10 were assessed by Western blotting. Long-term survival data were analyzed to assess the correlation between HELLPAR expression and patient prognosis. The binding interactions of HELLPAR/miR-448 and miR-448/ADAM10 were predicted and experimentally validated. Overexpression and knockdown constructs for HELLPAR, miR-448, and ADAM10 were transfected into NPC cells to assess their effects on proliferation, invasion, and apoptosis. Results HELLPAR and ADAM10 were significantly upregulated at both the RNA and protein levels in NPC tissues and cells, while miR-448 was notably downregulated. Suppression of HELLPAR inhibited NPC cell proliferation and invasion while promoting apoptosis. Mechanistically, HELLPAR functioned as a competitive endogenous RNA (ceRNA) by binding to miR-448, thereby downregulating its RNA expression. Overexpression of miR-448 counteracted the tumor-promoting effects of HELLPAR. Additionally, miR-448 directly targeted and suppressed ADAM10. Overexpression of ADAM10 reversed the inhibitory effects of miR-448 on NPC cell proliferation and invasion. Conclusion The HELLPAR/miR-448/ADAM10 axis plays a critical role in NPC progression. Suppressing HELLPAR expression enhances miR-448 activity, which in turn downregulates ADAM10 at both RNA and protein levels, leading to reduced NPC cell proliferation and invasion while promoting apoptosis.